Rawls's A theory of justice : a reader's guide - Lovett, Frank (Continuum reader's guides., 2011)
John Rawls's A Theory of Justice, first published in 1971,ïs arguably the most important work of moral and political philosophy of the twentieth century.Ä staple on undergraduate courses in political theory, it isä classic textïn which RawlsÈmakes an astonishing contribution to political and moral thought. È. Rawls's 'A Theory of Justice': A Reader's Guide offers a concise and accessible introduction to this hugely importantänd challenging work. Written specifically to meet the needs of students coming to Rawls for the first time, the book offers guidan.